Avaliação do potencial citotóxico das lectinas de Canavalia ensiformis, Canavalia brasiliensis e Cratylia floribunda - Martins, Gláucia Veríssimo Faheina (2009)
Lectins constitute a class of glycoproteins which are capable of binding carbohydrates selectively and reversibly, distinguishing small structural differences in complex oligosaccharides. Some studies have shown that binding of lectins to carbohydrate surface of normal and tumor cells leads to various biological effects such as, cell proliferation in normal lymphocytes and apoptosis in tumor cells. This study investigated the assessment of cytotoxic lectins of legumes Canavalia ensiformis (ConA), Canavalia brasiliensis (Conbr) and Cratylia floribunda (CFL) in normal, mouse peritoneal macrophage, and tumor cells. Initially the cytotoxic activity of the lectins was evaluated by reduction of tetrazolium (MTT) salt assay and measured the content of nucleic acids (CAN). ConA, Conbr and CFL not decreased the viability of peritoneal macrophages, but showed to be cytotoxic for J774, MCF-7, Molt-4 and HL-60 lineages. The MTT assay was more sensitive to the effects of lectins on cell viability and ConA was the most cytotoxic, followed by Conbr and CFL. The IC50 values ranged from around 10, 20 and 45μg/mL at ConA, Conbr and CFL respectively. The genotoxic potential of lectins was also evaluated using the comet assay, showing that proteins had a high rate of lesions in DNA from MCF-7, Molt-4 and H-60 cells, reaching a damage frequency exceeding 70% in concentration of 50 μg/mL for all lectins. The lectins caused morphological changes as assessed by differential staining with ethidium bromide and acridine orange, characteristic of apoptosis, and necrosis can be observed in higher lectin concentrations in tumor cell lines. In tests that evaluated the apoptosis, ConA, Conbr and CFL caused internucleossomal fragmentation, loss of membrane integrity which is characteristic of late apoptosis or necrosis, and mitochondrial depolarization. It was concluded that ConA, Conbr and CFL exhibited cytotoxicity to tumor cells causing cell death by apoptosis, therefore these proteins can be considered as a class of molecules with antitumor potential.